Functional Neuroimaging Correlates of Burnout among Internal Medicine Residents and Faculty Members - Durning, Steven J.; Costanzo, Michelle; Artino, Anthony R.; Dyrbye, Liselotte N.; Beckman, Thomas J.; Schuwirth, Lambert; Holmboe, Eric; Roy, Michael J.; Wittich, Christopher M.; Lipner, Rebecca S.; van der Vleuten, Cees (Frontiers in Psychiatry, 2013)
Burnout is prevalent in residency training and practice and is linked to medical error and suboptimal patient care. However, little is known about how burnout affects clinical reasoning, which is essential to safe and effective care. The aim of this study was to examine how burnout modulates brain activity during clinical reasoning in physicians. Using functional Magnetic Resonance Imaging (fMRI), brain activity was assessed in internal medicine residents (n=10) and board-certified internists (faculty, n=17) from the Uniformed Services University (USU) while they answered and reflected upon United States Medical Licensing Examination and American Board of Internal Medicine multiple-choice questions. Participants also completed a validated two-item burnout scale, which includes an item assessing emotional exhaustion and an item assessing depersonalization. Whole brain covariate analysis was used to examine blood-oxygen-level-dependent (BOLD) signal during answering and reflecting upon clinical problems with respect to burnout scores. Higher depersonalization scores were associated with less BOLD signal in the right dorsolateral prefrontal cortex and middle frontal gyrus during reflecting on clinical problems and less BOLD signal in the bilateral precuneus while answering clinical problems in residents. Higher emotional exhaustion scores were associated with more right posterior cingulate cortex and middle frontal gyrus BOLD signal in residents. Examination of faculty revealed no significant influence of burnout on brain activity. Residents appear to be more susceptible to burnout effects on clinical reasoning, which may indicate that residents may need both cognitive and emotional support to improve quality of life and to optimize performance and learning. These results inform our understanding of mental stress, cognitive control as well as cognitive load theory.